Auditory Event-Related Potentials in Antipsychotic-Free Subjects With Ultra-High-Risk State and First-Episode Psychosis - Hsieh, Ming H.; Lin, Yi-Ting; Chien, Yi-Ling; Hwang, Tzung-Jeng; Hwu, Hai-Gwo; Liu, Chih-Min; Liu, Chen-Chung (Frontiers in Psychiatry, 2019)
Background: Auditory event-related potentials (ERP) have been utilized to study defective information processing of patients with schizophrenia. To delineate the pathophysiological processes from pre-psychotic state to first episode psychosis, study on subjects from ultra-high risk state to first episode psychosis, ideally in an antipsychotic-free condition, can add important information to our understanding. Methods: Patients with ultra-high risk state (UHR) or at their first episode psychosis (FEP) who were drug-naive or only have been temporarily treated with antipsychotics were assessed by auditory ERPs measurement, including P50/N100 (sensory gating) and mismatch negativity (deviance detection). A group of age-matched healthy subjects serves as their controls. Results: A total of 42 patients (23 UHR and 19 FEP) and 120 control subjects were recruited, including 21pure drug-naïve and 21 with very short exposure to antipsychotics. Collapsing FEP and UHR as a patient group, they exhibited significant sensory deficits manifested as larger P50 S2 amplitude, larger N100 ratio, and smaller N100 difference, and significantly less deviance detection response revealed by MMN. Such differences were less significant when FEP and UHR were considered separately, yet seemingly a gradient of sensory gating deficits along the clinical severities revealed by P50/N100 findings could be seen. Conclusion: Our results were consistent with the majority of previous ERP studies, with or without controlling antipsychotic medication status, to show impaired sensory gating and deviance detection in pre- and early- psychotic states. The impact of antipsychotics on ERP seems to be ignorable in this early stage of psychosis, while a larger sample and a longitudinal study to follow the dynamic changes in ERP performance after taking antipsychotics will be needed to answer this question.